GAMBARAN MOTIVASI IBU ASUH DI SOS DESA TARUNA SEMARANG - Rr. Maria Kartika Sumanto (MANASA, 2014)
The aim of this study is to understand the motivation dynamics behind thedecision to become a care giver in SOS Desa Taruna Semarang using Maslow’sHierarchy of Motivation theoretical framework. Since they are not allowed to bemarriage when being a care giver, it is not an easy requirement to fulfill. There must be a strong motivation to commit with the requirement. Using qualitative approach, the participants of this study are care givers who have been worked at least for five years. A number of interviews and observations are applied. The results show that there is dynamic on the salient of safety needs and belongingness and love needs during the period of being a care giver. They need to consistently adaptive to deal with changes in the children situation.